ANÁLISE CONTRASTIVA DO USO DOS PRONOMES PESSOAIS EM ESPANHOL E PORTUGUÊS EM TEXTOS DE “MAFALDA” - Alves-Silva, Jamilson José (Intercâmbio, 2010)
This article aims to analyse the occurrence of personal pronouns in texts of Argentinean character Mafalda. In the light of Systemic-functional Grammar, a few questions shall be raised about what elements contribute to the occurrence of personal pronouns in both languages, mostly in the question of the hallidayan Reference concept.